10 Decreasing pain experienced by hospitalized pediatric patients by increasing the use of topical anesthetics for peripheral intravenous (PIV) line placement. (25th November 2019) - Lewis, Emilee; Waynik, Ilana; Mackey, Sarah
Abstract : Background: Venous access is a common source of pain for hospitalized patients. Topical anesthetics are effective at decreasing needle pain, can improve success rate, and decrease procedure time. At our institution, there is inconsistent use of topical anesthetics for PIV placement. Objectives: The global aim was to reduce pain experienced by hospitalized pediatric patients. The SMART aim was to increase topical anesthetic use for peripheral intravenous line (PIV) placement for hospitalized pediatric patients from a mean of 11% to 40% by June 2019. Methods: The project utilized the Model for Improvement. An institutional clinical pathway and PIV order set were developed. Pre-checked orders for anesthetics were added to order sets. Visual reminders for anesthetic and pathway use were placed on IV carts. Run charts were posted weekly on daily management system boards on each medical-surgical floor, and this data was shared at daily nursing huddles, to increase awareness of performance. Nurse managers provided individual feedback to nurses. Nursing scripting examples of how to discuss PIV placement and anesthetics with patients and families were placed on IV carts. Results: Topical anesthetic use for PIV placement increased from a mean of 11% to 34%. Comfort measures during PIV placement increased from a mean of 6% to 13%. PIV procedures with documentation of placement attempts increased from a mean of 47% to 60%. Conclusions: This project has highlighted the importance of pain prevention for needle procedures and initiated culture change. We have nearly reached our goal and PDSA cycles are ongoing to further increase topical anesthetic use. References: Friedrichsdorf et al. Pain outcomes in a US children's hospital: a prospective cross sectional survey. Hospital Pediatrics. 2015;5(1):18–26. Ammentorp J, Mainz J, Sabroe S. Parents' priorities and satisfaction with acute pediatric care. Arch Pediatr Adolesc Med . 2005;15(2):127–131. Cohen LL. Behavioral approaches to anxiety and pain management for pediatric venous access. Pediatrics . 2008;122 (3):S134–S139. Ammentorp J, Mainz J, Sabroe S. Parents' priorities and satisfaction with acute pediatric care. Arch Pediatr Adolesc Med . 2005;15 (2):127–131. Taddio A, Soin HK, Schuh S, Koren G, Scolnik D. Liposomal lidocaine to improve procedural success rates and reduce procedural pain among children: a randomized, controlled trial. CMAJ . 2005;172 (13):1691–1695. Zempsky WT. Optimizing the management of peripheral venous access pain in children: evidence, impact, and implementation. Pediatrics . 2008;122 (3):S121–S124. doi:10.1542/peds.2008-1055c Zempsky WT. Pharmacologic approaches for reducing venous access pain in children. Pediatrics . 2008;122 :S140. doi:10.1542/peds.2008-1055g Leahy S, Kennedy RM, Hesselgrave J, Gurwitch K, Barkey M, Millar TF. On the front lines: lessons learned in implementing multidisciplinary peripheral venous access pain- management programs in pediatric hospitals. Pediatrics . 2008;122 (9):S161–S170. doi:10.1542/peds.2008-1055i. Postier et al . Pain experience in a US children's hospital: a point prevalence survey undertaken after the implementation of a system-wide protocol to eliminate or decrease pain caused by needles." Hospital Pediatrics . 2018;8 (9):515–523.